CONCEPTUAL APPROACHES TO PUBLIC HEALTH PROTECTION IN THE REPUBLIC OF UZBEKISTAN - Mukhammedov Haidarali Melievich; Shavkat Mirziyoyev (Journals Park Publishing, 2023)
This article discusses the problems and main directions of improving the insurance market of the Republic of Uzbekistan. Today, the insurance market is one of the priorities in the country's economy. Uzbekistan pays attention to the development of health insurance, which once again underlines the importance of developing the insurance market. The insurance industry is undergoing significant transformations aimed at creating a new financial and economic system with multiple growth points. Therefore, the state develops not only a strategy for its socio-economic development, but also key strategic directions, which include the macroeconomic processes of insurance development, which play a crucial role in the domestic and global economy.
Keywords: Insurance, sphere, medicine, activities, law.